The efficacy of brief parent-infant psychotherapy for treating early regulatory disorders: a randomized controlled trial - Georg, Anna; Cierpka, Manfred; Schröder-Pfeifer, Paul; Kreß, Sandra; Taubner, Svenja (Journal of the American Academy of Child and Adolescent Psychiatry, 2021)
Early regulatory disorders (ERD) place considerable strain on the parent-infant relationship and are associated with high parental distress. Brief (4-session) psychodynamic-based focused parent-infant psychotherapy (fPIP) treats ERD by strengthening the quality of the parent-infant relationship. This randomized controlled trial investigates the efficacy of fPIP for treating ERD compared to standard pediatric care (treatment as usual [TAU]).